2013
DOI: 10.15288/jsad.2013.74.125
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap of Youth Violence Among Aggressive Adolescents with Past-Year Alcohol Use—A Latent Class Analysis: Aggression and Victimization in Peer and Dating Violence in an Inner City Emergency Department Sample

Abstract: The purpose of this study was to identify overlap and violence types between peer and dating aggression and victimization using latent class analysis (LCA) among a sample of aggressive adolescents with a history of alcohol use and to identify risk and protective factors associated with each violence class. Method: From September 2006 to September 2009, a systematic sample of patients (14-18 years old) seeking care in an urban emergency department were approached. Adolescents reporting any past-year alcohol use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 73 publications
7
53
1
2
Order By: Relevance
“…Some findings suggest that boys and girls use similar levels of both physical and emotional violence toward their partners (37)(38)(39) resulting in propositions that adolescent ADV demonstrates a greater degree of gender symmetry compared with adult partner violence where women are predominantly the victim. Although studies show that boys and girls use similar levels of physical violence toward their partners, different patterns emerge (36,38,39). Some evidence demonstrates that although girls use violence predominantly for self-defense, boys mainly use violence as the primary aggressor to exert control over their partner (38,40).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Some findings suggest that boys and girls use similar levels of both physical and emotional violence toward their partners (37)(38)(39) resulting in propositions that adolescent ADV demonstrates a greater degree of gender symmetry compared with adult partner violence where women are predominantly the victim. Although studies show that boys and girls use similar levels of physical violence toward their partners, different patterns emerge (36,38,39). Some evidence demonstrates that although girls use violence predominantly for self-defense, boys mainly use violence as the primary aggressor to exert control over their partner (38,40).…”
Section: Gender Differencesmentioning
confidence: 99%
“…Quando o adolescente sai da posição de ví-tima e passa a ser analisado nos estudos como o perpetrador da violência, a associação significativa entre o álcool e o comportamento violento foi verificada em grande parte dos estudos [1][2][3]10,14,15,20,21,23,29 . Isso pode ocorrer pelo fato dos adolescentes, sob efeito da bebida, perderem o senso crítico e se tornarem agressivos 10 .…”
Section: Discussionunclassified
“…A violência avaliada pelos entrevistados nos últimos 12 meses foi relacionada ao consumo de álcool nos últimos 30 dias. Adotar essa variação na referência pode trazer comprometimento à análise dos estudos, uma vez que as relações temporais são diferentes e expõem os indivíduos ao viés de memória, visto que os estudos que consideraram os eventos nos últimos 12 meses encontraram menos associação significativa do que os que consideraram entre 1 e 3 meses 2,3,10,14,15,18,20,21,23 . Alguns autores optaram por agrupar algumas variáveis estudadas.…”
Section: Discussionunclassified
“…in dating/partner relationships and peer/non-partner relationships, separately. 12,62 Weapon carriage during the past six-months was measured via two items assessing whether participants "carried a knife or razor" and/or "carried a gun." 63 Current gang affiliation was assessed via a question from the Tulane National Youth Study.…”
Section: Methodsmentioning
confidence: 99%
“…5 There is an extensive evidence-base regarding the association between substance use, mental health disorders, and a history of violence. [6][7][8][9][10][11][12][13][14][15][16][17][18] The few ED-based studies of youth with acute assault-injuries have reported high levels of depressive symptoms, [19][20][21][22][23] post-traumatic stress symptoms, 22,24 and alcohol/substance use. 19,22,25 Nonetheless, prior studies have been limited by: 1)the use of convenience samples; 2) the inclusion of only those with biological markers of substance use, alone; 3) interviewing patients long after the assault event took place; 4) the lack of use of diagnostic criteria for substance use/mental health disorders; 5) the lack of a non-injured comparison group of drug using youth.…”
Section: Introductionmentioning
confidence: 99%